Reliability of salivary cortisol and testosterone to a high-intensity cycling protocol to highlight overtraining - Hough, J.; Leal, D.; Scott, G.; Taylor, L.; Townsend, D.; Gleeson, M. (Journal of Sports Sciences, 2021)
Athletes physically overload to improve performance. Unbalanced stress/recovery may induce overtraining, which is difficult to diagnosis as no diagnostic marker exists. Hormonal responses to a 55/80 cycle (30-min of alternating blocks of 1-min at 55% and 4-min at 80% maximum work rate) may highlight early-stage overtraining (overreaching), as blunted cortisol and testosterone responses to 55/80 follows intensified training. However, the reliability of hormonal responses to 55/80 when not overreached is unknown. Therefore, reported blunted hormonal responses could be due to inconsistent cortisol and testosterone responses to 55/80. Participants (n = 23) completed three 55/80 bouts, >7 days apart, with no exercise 24 h pre-trials. Pre-exercise urine osmolality and stress questionnaire responses were measured. Pre, post, and 30-min post-exercise saliva samples were collected for cortisol and testosterone assessment. Salivary cortisol and testosterone responses, osmolality and well-being were not different between trials. Salivary cortisol and testosterone elevated from pre- to post-exercise [by 4.2 nmol.L-1 (cortisol) and 307 pmol.L-1 (testosterone)], and 30 min post-exercise [by 160 pmol.L-1 (testosterone) only]. Intraclass correlation coefficients for pre to peak post-exercise cortisol (0.89; good) and testosterone (0.53; moderate) were calculated. This demonstrates that 55/80 induces reliable elevations of salivary cortisol and testosterone when in a healthy state.